Ontogenetic shifts in the digestive tube and diet of Bryconamericus stramineus Eigenmann, 1908 (Osteichthyes, Characidae) - Suiberto, M.R.; Galuch, A.V.; Bialetzki, A.; Nakatani, K. (My University, 2009)
Aim: Studies on feeding of early life stages are very important to the understanding of the biology and trophic ecology of fish species. Therefore, the aim of this work is to describe the development of the digestive tube, and to characterize the diet of larvae and juveniles of Bryconamericus stramineus Eigenmann, 1908 of the upper Parana River floodplain; Methods: Larvae were obtained from, monthly samples during nychthemeral cycles with four-hour interval between samplings from February/91 to February/92, utilizing a conical-cylindrical plankton net; Results: At the preflexion stage, larvae at approximately 4.00 mm SL, showed a morphologically undifferentiated straight tube, with the anterior region more dilated. At the flexion stage a differentiation in the anterior region of the digestive tube occurs, with the intestine wall getting thicker (8.30 mm SL). The formation of pyloric caeca occurs at 9.00 mm SL. At the postflexion stage the first loop is formed at 9.25 mm SL and the second loop at about 10.00 mm SL. Bryconamericus stramineus consumed mainly cladocerans, also ingesting copepods, rotifers, nematodes, algae, insects and inorganic particles. Along the development, there was an increase in the number of food items and a diversification in the number of consumed taxa; Conclusions: Changes in the diet of B. stramineus larvae were not observed, being them zooplanktivores during all the initial development. However, an increase of large preys, such as insects larvae, was observed at the end of the larval period and in juveniles, suggesting a tendency towards invertivory. Larvae and juveniles preferentially fed during the night.
Mudanças ontogenéticas no tubo digestório e na dieta de Bryconamericus stramineus Eigenmann, 1908 (Osteichthyes, Characidae)